Factors affecting job satisfaction among executives : A case study in Sime Darby Research Sdn Bhd / Fadilah Mohamad Rosli - Mohamad Rosli, Fadilah (Bachelor of Science (Hons.) Statistics, 2015)
Job satisfaction among Sime Darby Research Sdn Bhd executives was highlighted by this study. The aim of this study was investigate the factors influencing on job satisfaction among Sime Darby Research Sdn Bhd executives. The dependent variable in this study was job satisfaction. The independent variables were promotional opportunities, remuneration, work-place environment, workload, social relationship with colleagues and management style. Survey method was used to collect data. The research instrument was a structured questionnaire. A stratified sampling technique was used to select the respondents for this study. A total of 125 executives of Sime Darby Research Sdn Bhd constituted the sample. The results shown that among the factors, that were remuneration, work-place environment, relationship with colleagues and management style were found to be significant predictors of job satisfaction contributing 75.5 percent of job satisfaction. The balance 24.5 percent was explained by the other factors. At the end of this study, it was found that the factors found only that remuneration, work-place environment, relationship with colleagues and management style that were contributed to the job satisfaction among executives in Sime Darby Research Sdn Bhd